Analisis Profitabilitas Bank Umum Go Public di Indonesia Sebelum dan Setelah Krisis : Internal dan Eksternal Faktor - Lindiasari S., Palupi; Undartik, Sri (Jurnal Ekonomi Kuantitatif Terapan, 2015)
This study aims to give the analysis of the determinants of 16 Indonesia go-public banking profitability over the periode 2005-2014. This study focus on the impact of internal factors (NIM, BOPO, CAR, LDR and NPL) and external factors (inflation, BIrate, IHSG and GDPdeflator) before and after crisis.  Furthermore, is to analize the simultaneous and growth effect of internal and external factors that have an influence to the profitability of go-public banking companies. Finally, is to give recommendation for managerial banking policy. This study using random effect method.  The empirical result shows that Indonesia go-public banking is influenced by several factor both internal and external factors.  After crisis CAR has positive and significant effect on ROA by 0,1 times larger than the effect of before crisis CAR. Whereas other internal factor (BOPO, NPL and NIM) give the same effect on ROA, both before and after crisis.  Bank ownership (DUMP) and LDR have no significant effect on ROA neither before nor after crisis.  External factor (Infation, BIrate and IHSG) are significant different effect on ROA’s before and after crisis condition.  Only GDPdeflator give the same effect on ROA both before and after crisis condition.  The recommendation from this result is managerial banking needed to reduce growth of internal factor that cause negatif side effect on ROA.
Keywords: Profitability banking; Internal Factor; External Factor; the condition of before or aftercrisis